Ensino de história e imprensa ilustrada: uso de charges como fonte histórica para a modalidade EJA em Ananás, TO - BARBOSA, Augusto César Ferreira (Universidade Federal do Tocantins, 2024)
This work articulates the use of Revista Illustrada magazine in the teaching of the history at elementary school. Such articulation unfolds in the design of a didactic sequence aimed at students of EJA, an adult education modality. The work materializes a research that mobilized varied authors interested the intersection of history teaching with didactics, besides relying upon specialized bibliography on historical analysis of printed sources. As the press is an important socio-cultural element that allows contact with contexts of past times, the research highlights the need to work with cartoon as historical evidence, given the richness of details, reflections and analyses useful to be used in classroom. Based on the research, a didactic sequence was designed, performed, and presented as model of a practice to complement activities elaborated by teachers in classroom.